[PP.19.11] PREHYPERTENSION PREVALENCE IN RUSSIA: THE RUSSIAN EPIDEMIOLOGY SURVEY ESSE-RF. (September 2016) - Erina, A.; Rotar, O.; Konradi, A.; Shalnova, S.; Balanova, Y.; Deev, A.; Zhernakova, I.U.; Oschepkova, E.; Karpov, Y.; Chazova, I.; Boytsov, S.; Shlyakhto, E.
Abstract : Objective: Prehypertension (PHT) is a precursor of hypertension (HT), associated with an increased risk of major cardiovascular-disease events. The study estimates prevalence of PHT in population-based sample of Russian Federation (RF) inhabitants. Design and method: A novel epidemiological survey of cardiovascular risk in regions of RF with different climatic, geographic, economic and demographic characteristics (ESSE-RF) was performed in a multi-step stratified random sample of approximately 1600 participants in 12 selected regions (Volgograd, Vologda, Voronezh, Vladivostok, Ivanovo, Kemerovo, Krasnoyarsk, Orenburg, Tomsk, Tyumen, Saint-Petersburg and Northern Osetia-Alania). Totally 20652 participants aged 25–65 years were recruited. All subjects signed informed consent and filled validated questionnaires regarding lifestyle, concomitant disease and medication. Anthropometry, fasting blood sampling, blood pressure (BP) measurement were performed. Office BP was registered by OMRON (Japan) twice on right hand in sitting position with calculation of mean BP. Optimal BP was detected as BP less 120/80 mmHg, PHT as BP = 120–139/80–89 mmHg, HT as BP higher (or equal) 140/90 mmHg or antihypertensive treatment. Statistical analysis was performed using SPSS Statistics 20. Results: Data analysis was possible in 20607 participants (7806 males (37, 9%) and 12801 females (62, 1%)), results are presented in Table 1. Figure. No caption available. Conclusions: Prehypertension was detected in 1/3 of participants in the selected age group. Males have prehypertension significantly more often than females. While prevalence of hypertension increases with age, prevalence of prehypertension and optimal BP decreases. In the youngest age group prehypertension was registered significantly more often than optimal BP. Half of population in age 45–54 has hypertension and 1/3 prehypertension.